Kedudukan Ekspedisi Kotag Cargo dalam Perspektif Hukum Perlindungan Konsumen dan Hukum Pengangkutan - Abdul Mutalib Abdul Aziz; Roy Marthen Moonti; Ibrahim Ahmad (Hukum Inovatif : Jurnal Ilmu Hukum Sosial dan Humaniora, 2026)
The development of digital trade and interregional goods distribution has increased public demand for expedition services that are fast, safe, transparent, and accountable. Kotag Cargo, as a shipping service provider, has a legal relationship with consumers, particularly when delays, damage, loss, or discrepancies in delivery services occur. This study aims to analyze the legal position of Kotag Cargo from the perspective of consumer protection law and transportation law, as well as to examine the forms of legal protection and corporate liability when consumers suffer losses. This research uses a normative juridical method by examining statutory regulations, legal principles, doctrines, and relevant literature. The results show that Kotag Cargo may be positioned as a shipping service business actor, freight forwarder, carrier, or intermediary, depending on its factual role in the delivery process. However, any such legal position does not eliminate its legal responsibility toward consumers. Legal protection is provided preventively through clear information and repressively through claim mechanisms and compensation. It is recommended that Kotag Cargo clarify its service clauses, claim procedures, delivery standards, and compensation mechanisms so that consumer rights are protected fairly and transparently.